2021
DOI: 10.3389/fpubh.2021.627312
|View full text |Cite
|
Sign up to set email alerts
|

Geographical Variation of COPD Mortality and Related Risk Factors in Jiading District, Shanghai

Abstract: Background: Chronic obstructive pulmonary disease (COPD) is the fourth leading cause of death in China. Although numerous studies have been conducted to determine the risk factors for COPD mortality such as ambient air pollution, the results are not fully consistent.Methods: This study included mortality analysis and a case-control design by using the data extracted from the Mortality Registration System in Jiading District, Shanghai. Traditional logistic regression, geographically weighted logistic regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
(39 reference statements)
1
2
0
Order By: Relevance
“…Their study showed a significant association between proximity to main roads and prevalence of COPD, suggesting that proximity to road traffic may be a risk factor for developing COPD. Similar observations have been reported in the past from France,[ 2 ] Japan,[ 3 ] China,[ 4 ] and Germany. [ 5 ] Several studies have shown that, residing close (<100 m) to a major road has a detrimental effect on lung function and can increase the risk of allergic diseases and asthma.…”
supporting
confidence: 90%
“…Their study showed a significant association between proximity to main roads and prevalence of COPD, suggesting that proximity to road traffic may be a risk factor for developing COPD. Similar observations have been reported in the past from France,[ 2 ] Japan,[ 3 ] China,[ 4 ] and Germany. [ 5 ] Several studies have shown that, residing close (<100 m) to a major road has a detrimental effect on lung function and can increase the risk of allergic diseases and asthma.…”
supporting
confidence: 90%
“…Geographical differences in COPD incidence, mortality, and prevalence have been reported in other countries [16][17][18][19][20][21], and factors associated with these regional differences have been identified. A study in Taiwan has reported that factors such as smoking prevalence, percentage of aborigines, and concentration of particulate matter 10 are positively associated with regional COPD mortality rate [20], and another study in China has showed that smoking and exposure to particulate matter 2.5 are positively associated with COPD prevalence [18].…”
Section: Introductionmentioning
confidence: 83%
“…A study in Taiwan has reported that factors such as smoking prevalence, percentage of aborigines, and concentration of particulate matter 10 are positively associated with regional COPD mortality rate [20], and another study in China has showed that smoking and exposure to particulate matter 2.5 are positively associated with COPD prevalence [18]. Another study that investigated factors associated with COPD mortality in Shanghai has revealed that extremely low temperatures in the month before death, shorter distances to the highway, and lower gross domestic product are associated with mortality [21]. Therefore, socioeconomic and environmental characteristics are particularly associated with regional COPD mortality or prevalence in other countries.…”
Section: Introductionmentioning
confidence: 99%